Earth's metamorphic secular evolution accessed by rutile - Cerri, Rodrigo I. [UNESP]; Spencer, Christopher; Caxito, Fabrício de Andrade; Luvizotto, George Luiz [UNESP]; Moraes, Renato; Riccomini, Claudio; Puetz, Stephen J. (Elsevier, 2024)
Rutile provides crucial insights into the evolution of plate tectonics and variations in tectonomagmatic modes over Earth's history primarily because rutile predominantly tracks higher-pressure metamorphism (>1.0–1.2 GPa). Comparison of rutile age and compositional data with diverse proxies tracks the presence of low temperature/pressure (T/P) metamorphic conditions, enabling the tracing of plate tectonics onset and evolution. We present a new compilation of rutile U-Pb ages that lag zircon ages by approximately 50 Myr, potentially indicating cooling ages of metamorphic belts. The earliest rutile age peak (ca. 1.8 Ga) aligns with the oldest evidence for low T/P metamorphic conditions. This coincides with a shift in the T/P distribution of rutile whereas the T/P of Archean rutile forms a tight normal distribution. In the Paleoproterozoic, the rutile T/P distribution is skewed to lower T/P, following the broader pattern of the full metamorphic record. The degree of lower T/P skew increases through time until the lower T/P population dominates the rutile record from the Neoproterozoic to the present. These data further highlight shifts in dominant metamorphic modes that can be tied to the evolution of the tectonic system, with early Archean metamorphism being associated with plume-driven vertical tectonics or hot, shallow subduction and post-Archean metamorphism being associated with progressive less plume-driven vertical tectonics and colder, steeper subduction. Although the frequency of rutile is lower during the Mesoproterozoic, the rutile T/P during this time follows the progressive skewing pattern from the Paleoproterozoic to the present and is likely inconsistent with a phase of interrupted tectonics characterized by stagnant lid.
Keywords: Geodynamics; Plate tectonics; Rutile; Secular evolution; Subduction; T/P metamorphism